Co‐registration of angiography and intravascular ultrasound images through image‐based device tracking. Issue 7 (28th November 2015) - Prasad, Megha; Cassar, Andrew; Fetterly, Kenneth A.; Bell, Malcolm; Theessen, Heike; Ecabert, Olivier; Bresnahan, John F.; Lerman, Amir
Abstract : Objectives: To determine the feasibility of automated co‐registration of angiography and intravascular ultrasound (IVUS) to facilitate integration of these two imaging modalities in a synchronous manner. Background: IVUS provides cross‐sectional imaging of coronary arteries but lacks overview of the vascular territory provided by angiography. Co‐registration of angiography and IVUS would increase utility of IVUS in the clinical setting. Methods: Forty‐nine consecutive patients undergoing surveillance for cardiac allograft vasculopathy with angiography and IVUS of the left anterior descending artery (LAD) were enrolled. A pre‐IVUS angiogram of the LAD was performed followed by an ECG‐triggered fluoroscopy (ECGTF) during IVUS pullback at 0.5 mm/s using an automatic pullback device. ECGTF was used to track the IVUS catheter during pullback and establish a spatial relationship to the pre‐IVUS angiogram. Angio‐IVUS co‐registration was performed with a research prototype (Siemens Healthcare, Germany) and accuracy was evaluated by distance mismatch between angiography and IVUS images at vessel bifurcations. Results: Median age was 54 (44.5, 67) years. The population was 82.6% male with minimal risk factors. The median (IQR) co‐registration distance mismatch measured at 108 bifurcations in 42 (85%) patients was 0.35 (0.00–1.16) mm. Seven patients were excluded due to inappropriate data acquisition ( n  = 3) and failure of tracking ( n  = 4), e.g., due to overlapping sternal wires. Estimated effective radiation dose for ECGTF was 0.09 mSv. Conclusion: This study demonstrates the feasibility of angio‐IVUS co‐registration which may be used as a clinical tool for localizing IVUS cross‐sections along an angiographic roadmap. © 2015 Wiley Periodicals, Inc.